2022
DOI: 10.1101/2022.07.14.499901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pollinator Grooming Behavior Alters Pollen Landscapes on Bees’ Bodies and Increases Pollen Carryover to Other Flowers

Abstract: Pollen participates both as the carrier of male gametes in the reproduction of flowering plants and as a key resource exploited by floral visitors, especially bees. Pollinator behavior significantly alters the patterns of pollen removal and deposition, often called pollen fates. To date, few theoretical investigations have attempted to jointly model patterns of pollen transfer and pollinator behavior, and empirical studies are restricted to species to which pollen movement can be tracked. Here we use a spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Our findings are the first indication that nongrooming behavior could increase siring success. Yet other research suggests increased grooming behavior increases pollen carryover because it “stirs” the pollen on the bee's body so that not just pollen from the most recent flower is “on top” and able to be deposited (Marcelo et al, 2022 [preprint]). Thus, it is still unclear how nongrooming behavior impacts pollen carryover, though the increased siring success from male bee visits in this study could indicate increased pollen carryover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are the first indication that nongrooming behavior could increase siring success. Yet other research suggests increased grooming behavior increases pollen carryover because it “stirs” the pollen on the bee's body so that not just pollen from the most recent flower is “on top” and able to be deposited (Marcelo et al, 2022 [preprint]). Thus, it is still unclear how nongrooming behavior impacts pollen carryover, though the increased siring success from male bee visits in this study could indicate increased pollen carryover.…”
Section: Discussionmentioning
confidence: 99%
“…More research on pollen carryover in this system could help to elucidate the reason. For example, V. G. Marcelo et al (2022 [preprint]) found that grooming bees have increased pollen carryover and thus greater diversity in their deposited pollen. Therefore, in our system, a grooming bee like A. helianthiformis might deposit diverse, high‐quality pollen that sets a lot of seeds (increasing female fitness), but the high diversity of the pollen load means that few seeds are set by any one sire's pollen per visit (average impact on male fitness).…”
Section: Discussionmentioning
confidence: 99%
“…Pollinator foraging and grooming behavior once on or after visiting a flower likely also impacts pollen-associated virus transmission because these behaviors determine pollen transfer from anther to stigma. For instance, Russell et al (2019Russell et al ( , 2021 found that bumble bees collecting pollen via "scrabbling" transferred more pollen grains and epiphytic bacterial cells to stigmas than bees only collecting nectar, and Marcelo et al (2023) predict that grooming allows bees to acquire more pollen grains and deposit a more diverse assemblage of pollen grains while foraging. Thus, withinflower foraging and grooming behaviors could mediate the transmission of epiphytic viruses and pollen-associated ones.…”
Section: Pollinator Traitsmentioning
confidence: 99%
“…The structures of these landscapes can theoretically affect the distance and timing of a flower's pollen dispersal (Harder and Wilson, 1998), with potentially far‐reaching effects on floral evolution and ecology. For example, layering may increase gene flow if pollen is not removed immediately from pollinators by stigmas, but is instead buried underneath subsequently deposited pollen, only to resurface much later (Lertzman and Gass, 1983; Morris et al, 1995; Marcelo et al 2022 [preprint]). Pollen landscapes may also generate variability in the ability of pollen grains to adhere to or leave the bodies of pollinators.…”
Section: Figurementioning
confidence: 99%